Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Min-Max - Andri C. R Kussing; Asih Ahistasari; Tamrin Tajuddin (Industrial Engineering Journal – System, 2022)
This study aims to determine the amount of raw material inventory. This research will be carried out at UMKM Blessings Fillet Jalan Victory km 10. The Min Max method, the Min–Max method is a method of controlling raw materials based on the assumption that if the inventory has passed the minimum limits and is approaching the limit of the Safety Stock or the limit of the safety stock. , then Reorder or reorder raw materials. The maximum and minimum inventories, respectively, for anchovy ingredients obtained were 1,583,2 kg and 1,030 kg, respectively. And from the data obtained in the results of this research at the UMKM Berkah villet, there is a large supply of raw materials using a min-max of 553.2 Kg.